2014
DOI: 10.1177/0095798414562067
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Ethnic Variation in the Relationship Between Stress, Social Networks, and Depressive Symptoms Among Older Black Americans

Abstract: The relationship between different types of stressors and depressive symptoms among older Black populations is poorly understood. Even less is known about the social networks that might buffer different stressors on individuals within Black ethnic groups. The purpose of this study was to examine whether there are differences in the relationship between stress and social networks on depressive symptoms by ethnic group while ethnicity functioned as a proxy for culture. Data were drawn from the National Survey of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Consistent with findings from previous research, both cross-sectional ( Marshall-Fabien & Miller, 2014 ) and longitudinal ( English et al, 2014 ), we found that more frequent experiences of everyday discrimination are associated with more depressive symptoms in older African Americans over time. These findings suggest that everyday discrimination can be perceived as a stressor that negatively affects mental health.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with findings from previous research, both cross-sectional ( Marshall-Fabien & Miller, 2014 ) and longitudinal ( English et al, 2014 ), we found that more frequent experiences of everyday discrimination are associated with more depressive symptoms in older African Americans over time. These findings suggest that everyday discrimination can be perceived as a stressor that negatively affects mental health.…”
Section: Discussionsupporting
confidence: 91%
“…Despite that fewer studies focused on older adults, one study using data from the Health and Retirement Study (HRS) found that everyday discrimination was associated with more frequent depressive symptoms among older African Americans, who also reported higher rates of both lifetime and everyday discrimination than older whites and Hispanics ( Ayalon & Gum, 2011 ). Everyday discrimination is also strongly associated with more frequent symptoms of psychological distress ( Nguyen, Taylor et al, 2017 ) and depressive symptoms ( Marshall-Fabien & Miller, 2014 ) among older adults in the NSAL. Some evidence suggests that among older adults, everyday discrimination, as a chronic stressor, is more strongly associated with mental health outcomes than major lifetime discrimination ( Ayalon & Gum, 2011 ).…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Several reviews and numerous studies provide compelling evidence showing that perceived discrimination adversely affects mental health ( 10–17 ). Findings from studies illustrate that reporting high levels of racial and nonracial forms of perceived discrimination is associated with elevated depressive symptoms ( 18–21 ). Perceived discrimination, subjective perceptions of unfair or unjust treatment based on personal characteristics (e.g., race/ethnicity, age, sex, weight, sexual orientation, and other characteristics) ( 22 ), is more frequently reported by African Americans, regardless of attribution ( 23–26 ).…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Of the 43 included studies, 13 were published in health outcome-specific journals [ 25 , 33 , 35 , 37 , 38 , 42 , 44 , 47 , 51 , 56 , 58 , 59 , 62 ] (e.g., Breast Cancer Research and Treatment ), 15 in aging-specific journals [ 21 , 22 , 24 , 28 , 30 , 32 , 34 , 36 , 45 , 53 – 55 , 57 , 60 , 61 ] (e.g., Journals of Gerontology ), four in racial disparities or race-specific journal [ 23 , 41 , 49 , 52 ] (e.g., Journal of Racial and Ethnic Health Disparities ) and the remainder in general health and social science journals [ 26 , 27 , 29 , 31 , 39 , 40 , 43 , 46 , 48 , 50 , 64 ] (e.g., PLOS One ).…”
Section: Resultsmentioning
confidence: 99%